Athlete level, sport-type, and gender influences on training, mental health, and sleep during the early COVID-19 lockdown in Malaysia - Washif, Jad Adrian; Kok, Lian-Yee; James, Carl; Beaven, Christopher Martyn; Farooq, Abdulaziz; Pyne, David B.; Chamari, Karim (Frontiers in Physiology, 2023)
Purpose: We evaluated the extent of changes in training practices, recovery, mental health, and sleep patterns of athletes during the early COVID-19 lockdown in a single country-cohort. Methods: A total of 686 athletes (59% male, 41% female; 9% World Class, 28% International, 29% National, 26% State, 8% Recreational) from 50 sports (45% individual, 55% team) in Malaysia completed an online, survey-based questionnaire study. The questions were related to training practices (including recovery and injury), mental health, and sleep patterns. Results: Relative to pre-lockdown, training intensity (−34%), frequency (−20%, except World-Class), and duration (−24%–59%, especially International/World-Class) were compromised, by the mandated lockdown. During the lockdown, more space/access (69%) and equipment (69%) were available for cardiorespiratory training, than technical and strength; and these resources favoured World-Class athletes. Most athletes trained for general strength/health (88%) and muscular endurance (71%); and some used innovative/digital training tools (World-Class 48% vs. lower classification-levels ≤34%). More World-Class, International, and National athletes performed strength training, plyometrics, and sport-specific technical skills with proper equipment, than State/Recreational athletes. More females (42%) sourced training materials from social media than males (29%). Some athletes (38%) performed injury prevention exercises; 18% had mild injuries (knees 29%, ankles 26%), and 18% received a medical diagnosis (International 31%). Lower-level athletes (e.g., State 44%) disclosed that they were mentally more vulnerable; and felt more anxious (36% vs. higher-levels 14%–21%). Sleep quality and quantity were “normal” (49% for both), “improved” (35% and 27%), and only 16% and 14% (respectively) stated “worsened” sleep. Conclusion: Lockdown compromised training-related practices, especially in lower-level athletes. Athletes are in need of assistance with training, and tools to cope with anxiety that should be tailored to individual country requirements during lockdown situations. In particular, goal-driven (even if it is at home) fitness training, psychological, financial, and lifestyle support can be provided to reduce the difficulties associated with lockdowns. Policies and guidelines that facilitate athletes (of all levels) to train regularly during the lockdown should be developed.